Interleukin‐10 negatively modulates extracellular signal‐regulated kinases 1 and 2 in aorta from hypertensive mouse induced by angiotensin II infusion. (7th September 2018) - Bressan, Alecsander F.; Fonseca, Gisele A.; Tostes, Rita C.; Webb, R. Clinton; Lima, Victor Vitorino; Giachini, Fernanda Regina
Abstract: The activation of extracellular signal‐regulated kinase 1 and 2 (ERK 1/2) pathway promotes increased vascular contractility in angiotensin II (Ang II)‐induced hypertensive mice. Interleukin‐10 (IL‐10) is an immune‐regulatory cytokine with the ability to prevent vascular hypercontractility during hypertension. We hypothesized that IL‐10 would downregulate vascular ERK 1/2 activation during Ang II‐induced hypertension. Wild‐type (WT) or IL‐10 knockout (IL‐10 −/− ) mice received Ang II infusion (90 ηg.min) or vehicle (saline), via osmotic mini‐pumps (0.25 μL/h for 14 days), whereas another WT group were infused with exogenous IL‐10 (0.5 ηg/min, 14 days) simultaneously, or not, with Ang II. Aortic rings were mounted in a myograph, and concentration‐response curves to phenylephrine were evaluated, in the presence or absence of ERK 1/2 inhibitor (PD98059, 10 μm, 40 min). Protein expression of vascular ERK 1/2 was determined by Western blot. Ang II infusion increased the maximal contractile response in both WT and IL‐10 −/− mice. Concomitant infusion of IL‐10 and Ang II prevented hypercontractility in the vasculature. Exogenous IL‐10 infusion prevented ERK 1/2 activation and hypercontractility, induced by Ang II. These findings suggest that IL‐10 negatively modulates ERK 1/2 activation and prevents hypercontractility during Ang II‐induced hypertension.